Dependence of Cellulase Induced Resistance to Alamethicin (CIRA) on Membrane Lipid Modification (s) in Arabidopsis thaliana - Holla,Sanjana (2018)
Fungi belonging to the genus Trichoderma are filamentous and soilborne, and are usually known for their plant growth-stimulating effects. Trichoderma viride is one of the species belonging to the genus, and is recognized as a plant symbiont known to improve plant growth and pathogen protection. Trichoderma species produce certain antifungal and antibiotic agents called peptaibols, as secondary metabolites. Alamethicin is a peptaibol produced by the fungus T. viride. Alamethicin has been a model peptide to study ion channel assembly, voltage gating, and peptide-membrane interactions. It is also widely used as an agent to induce various physiological and defense responses in plants and as a tool for cell permeabilization. Alamethicin forms voltage-gated ion channels in the lipid bilayers of membranes including those of the host plant cells. However, pretreatment of plant cells with cellulase(s) produced by T. viride induces resistance to alamethicin permeabilization. Previous studies suggest that this resistance may be due to modifications in the lipid membrane constituents. The aim of this research project was to utilize Arabidopsis mutants to investigate the dependence of Cellulase Induced Resistance to Alamethicin (CIRA) on the plasma membrane lipid composition in Arabidopsis roots. Through this project, we preliminarily categorized 21 Arabidopsis mutants based on the gene types, gene families, protein location and gene expression using bioinformatics databases. Special emphasis was given on studying the psd3 mutants and to understand what proteins/pathways are involved in making this mutant deficient in CIRA. Through this research project, we categorized the CIRA mutant genes based on the proteins involved in lipid metabolic processes, Ca2+ signaling pathways and cell wall-related proteins, which suggests a potential mechanism for plant tolerance to Trichoderma needed for mutualistic symbiosis.